1986
DOI: 10.1128/mcb.6.12.4149-4154.1986
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 2 Peptide IX Gene Is Expressed Only on Replicated DNA Molecules

Abstract: Transcription of the adenovirus type 2 peptide IX (pIX) gene was examined in transient expression assays. When a nonreplicating plasmid DNA containing the pIX gene was introduced into HeLa cells by the DEAE-dextran method, no pIX gene transcript was detected. In contrast, efficient transcription was observed in the cells transfected with a replicating plasmid containing the pIX gene. Adenovirus early genes did not affect the level of transcription of the pIX gene on either a nonreplicating or a replicating pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…By using the same assay, i.e., transient transfection of HeLa cells, similar results to those presented here for the Xenopus (-globin gene have been obtained for the adenovirus pIX gene (33,47). This gene is expressed in vivo after the onset of viral DNA replication, and superinfection experiments had previously demonstrated that the delayed expression of this gene could not be overcome simply by supplying early gene products in trans (8,43).…”
Section: Discussionsupporting
confidence: 76%
“…By using the same assay, i.e., transient transfection of HeLa cells, similar results to those presented here for the Xenopus (-globin gene have been obtained for the adenovirus pIX gene (33,47). This gene is expressed in vivo after the onset of viral DNA replication, and superinfection experiments had previously demonstrated that the delayed expression of this gene could not be overcome simply by supplying early gene products in trans (8,43).…”
Section: Discussionsupporting
confidence: 76%